2010
DOI: 10.3862/jcoloproctology.63.499
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Adenocarcinoma of the Sigmoid Colon with Pelvic Arteriovenous Malformation

Abstract: F i g . 1 C o l o n o s c o p y r e v e a l e d a t y p e -2 t u mo r s u r r o u n d i n g t h e s i g mo i d c o l o n ; t h e a n a l e d g e o f t h e t u mo r wa s l o c a t e d 3 0 c m f r o m t h e a n a l v e r g e .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…We were eventually able to treat it without bleeding complication by preceding IVR for APF. Two cases in the left-side colorectal cancer with comorbid abnormal vessel communications in pelvis are reported in Table 1 [40, 41]. However, both clearly differentiated from our case because the nidi were located in internal iliac region, and main in- and outflow vessels were related to systemic circulation.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…We were eventually able to treat it without bleeding complication by preceding IVR for APF. Two cases in the left-side colorectal cancer with comorbid abnormal vessel communications in pelvis are reported in Table 1 [40, 41]. However, both clearly differentiated from our case because the nidi were located in internal iliac region, and main in- and outflow vessels were related to systemic circulation.…”
Section: Discussionmentioning
confidence: 60%
“…Inferior APF consists not only of the inferior mesenteric artery and vein but also complex vessels such as the internal iliac, inferior mesenteric, and median sacral artery and vein. The differential diagnosis of inferior APF of the pelvic AVM in the internal iliac perfusion regions is often difficult [40, 41]. Angiography is essential to assess every blood flow and the presence of nidus and vascular fistulas.…”
Section: Discussionmentioning
confidence: 99%
“…Since Margulis et al first reported on gastrointestinal AVMs in 1960, the number of reported cases of AVM has increased due to the widespread use of colonoscopy and increase in the number of elderly people with arteriosclerosis [7] . Its causes are broadly divided into congenital, due to abnormal vascular development during the embryonic period, and acquired, due to trauma, surgery, pregnancy and delivery [1] . Most gastrointestinal AVMs are solitary, occurring predominantly in the stomach, small intestine and right colon, and rarely in the IMA region [2] .…”
Section: Discussionmentioning
confidence: 99%
“…An arteriovenous malformation (AVM) is defined as a vascular malformation with a short, non-capillary communication between the arteries and veins [1] . Gastrointestinal AVMs occur most often in the stomach, small intestine and right colon, and only rarely in the inferior mesenteric artery (IMA) region [2] .…”
Section: Introductionmentioning
confidence: 99%